2002
DOI: 10.1128/aem.68.3.1374-1380.2002
|View full text |Cite
|
Sign up to set email alerts
|

Hindgut Fermentation in Three Species of Marine Herbivorous Fish

Abstract: Symbioses with gut microorganisms provides a means by which terrestrial herbivores are able to obtain energy. These microorganisms ferment cell wall materials of plants to short-chain fatty acids (SCFA), which are then absorbed and used by the host animal. Many marine herbivorous fishes contain SCFA (predominantly acetate) in their hindgut, indicative of gut microbial activity, but rates of SCFA production have not been measured. Such information is an important prerequisite to understanding the contribution t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
156
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(170 citation statements)
references
References 42 publications
12
156
1
1
Order By: Relevance
“…Molecular genetic techniques offer the ability to identify and delineate fish stock structure where it may not be apparent from phenotypic or behavioural characteristics (Storm and Ringo, 2013). Such techniques have been used successfully to understand the structure of marine fish species (Mountfort et al, 2002;Nelson et al, 2003;Ismail et al, 2008;Jageethadevi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Molecular genetic techniques offer the ability to identify and delineate fish stock structure where it may not be apparent from phenotypic or behavioural characteristics (Storm and Ringo, 2013). Such techniques have been used successfully to understand the structure of marine fish species (Mountfort et al, 2002;Nelson et al, 2003;Ismail et al, 2008;Jageethadevi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Fish were among the earliest jawed vertebrates to evolve many adaptive immune features that are hallmarks of mammalian systems (Flajnik and Du Pasquier, 2004) and, thus, the known interplay between immunity and mammalian gut bacteria (Hooper et al, 2012) suggests the potential for similar symbioses in rayfinned fish. Fish gut bacteria are generally related to animal-associated microbes, and marine herbivorous fish harbor communities that resemble those of other vertebrates, including gut-fermenting mammals (Mountfort et al, 2002;Sullam et al, 2012). Although community composition across fish species shows correlations with habitat salinity and feeding ecology (Ringø and Strøm, 1994;Ringø and Olsen, 1999;Sullam et al, 2012), a small number of recent surveys have provided glimpses into intraspecific variation in fish gut bacteria and have indicated that there are differences across more distantly related individuals and sampling locations and a sex-dependent effect of diet on gut microbiota (Wilson et al, 2008;Roeselers et al, 2011;Navarrete et al, 2012;Bolnick et al, 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…It is becoming clear that non-ruminant consumers may also rely on microbial gut contributions under certain conditions. More research into the role of the gut microbial community in consumer amino acid metabolism is warranted, particularly for species such as sea turtles, dugongs and herbivorous fishes that are known to have extensive gut microbe communities (e.g., Mountfort et al 2002, Andre et al 2005.…”
Section: Amino Acids Carbonmentioning
confidence: 99%